Implementasi Kebijakan Izin Usaha Mikro dan Kecil (IUMK) di Kecamatan Denpasar Barat - Krisna Dewi, Gusti Ayu; Yasintha, Putu Nomy; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTRACT The Micro and Small Business License Policy (IUMK) in West Denpasar District has been running since February of 2015. West Denpasar District became the first district to implement IUMK and has adequate facilities, but the number of IUMK’s publishing in West Denpasar District is still slightly compared to 3 (three) other districts in Denpasar City. The purpose of this IUMK is to make it easier for people to get legality for their business and easy access to empowerment, such as access to capital or financial. The purpose of this research is to know the implementation of policy of Small and Micro Business License (IUMK) in West Denpasar District by using Policy Implementation Theory from Charles O. Jones, including organization, interpretation, and application. This research used a descriptive qualitative method with data collection techniques such as observation, interview, dan documentation. The result of this research is the implementation of IUMK in West Denpasar District has been running well from the policy supporting organization aspect, but still need to be improved on the interpretation aspect of the implementation of IUMK and the lack of socialization, and the application or implementation aspect of IUMK. Through the improvement of the overall policy implementation process, it is expected to be able to increase the number of IUMK publishing as an effort to empower micro and small business enterprises in West Denpasar District. Keywords: Implementation, Business License, SMEs